Comparison of Patellofemoral Kinematics and Stability After Medial Patellofemoral Ligament and Medial Quadriceps Tendon–Femoral Ligament Reconstruction. Issue 9 (July 2020) - Spang, Robert; Egan, Jonathan; Hanna, Philip; Lechtig, Aron; Haber, Daniel; DeAngelis, Joseph P.; Nazarian, Ara; Ramappa, Arun J.
Background: There is a lack of evidence regarding the optimum extensor-sided fixation method for medial patellofemoral ligament (MPFL) reconstruction. There is increased interest in avoiding patellar drilling via soft tissue–only fixation to the distal quadriceps, thus reconstructing the medial quadriceps tendon–femoral ligament (MQTFL). The biomechanical implications of differing extensor-sided fixation constructs remain unknown. Hypothesis: The null hypothesis was there would be no differences between traditional MPFL reconstruction and MQTFL reconstruction with respect to resistance to lateral translation, patellar position, or patellofemoral contact pressures. Study Design: Controlled laboratory study. Methods: Nine adult knee specimens were mounted on a jig that applied static, physiologic loads to the quadriceps tendons. Patellar position and orientation, knee flexion angle, and patellofemoral pressure were recorded at 8 different flexion angles between 0° and 110°. Additionally, a lateral patellar excursion test was conducted wherein a load was applied directly to the patella in the lateral direction with the knee at 30° of flexion and subjected to 2-N quadriceps loads. Testing was conducted under 4 conditions: intact, transected MPFL, MQTFL reconstruction, and MPFL reconstruction. For MQTFL reconstruction, the surgical technique established by Fulkerson was employed. For MPFL reconstruction, a traditional technique was utilized. Results: The patellar excursion test showed no significant difference between the MQTFL and intact states with respect to lateral translation. MPFL reconstruction led to significantly less lateral translation ( P < .05) than all other states. There were no significant differences between MPFL and MQTFL reconstructions with respect to peak patellofemoral contact pressure. MPFL and MQTFL reconstructions both resulted in increased internal rotation of the patella with the knee in full extension. Conclusion: Soft tissue-only extensor-sided fixation to the distal quadriceps (MQTFL) during patella stabilization appears to re-create native stability in this time 0 cadaver model. Fixation to the patella (MPFL) was associated with increased resistance to lateral translation. Clinical Relevance: Evolving anatomic knowledge and concern for patellar fracture has led to increased interest in MQTFL reconstruction. Both MQTFL and MPFL reconstructions restored patellofemoral stability to lateral translation without increasing contact pressures under appropriate graft tensioning, with MQTFL more closely restoring native resistance to lateral translation at the time of surgery.